The complete chloroplast genome of Desmodium uncinatum (Fabaceae). Issue 3 (4th March 2021) - Yi, Dengxia; Jiang, Wenbo; Ma, Lin; Pang, Yongzhen
Abstract: Desmodium uncinatum is one of the most important legume forage which distributes in tropical and subtropical regions of the world. In our study, we obtained the complete chloroplast genome of D. uncinatum with a length of 148, 853 bp, including a large single copy region of 84, 019 bp, small single copy region of 18, 223 bp, and a pair of inverted repeat regions of 20, 672 bp. The GC content in the whole chloroplast genome of D. uncinatum is 35.16%. Among the 133 unique genes in the circular genome, 37 tRNA, 12 rRNA and 84 protein-coding genes were successfully annotated. We constructed the Maximum likelihood (ML) tree with 11 species, and came to the conclusion that D. uncinatum was phylogenetically closely related to the genus of Glycine and Trifolium .